2005
DOI: 10.1007/s00380-005-0847-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the cavotricuspid isthmus and right atrium by multidetector-row computed tomography in patients with common atrial flutter

Abstract: The sizes of the right atrium (RA), cavotricuspid isthmus, and Eustachian valve are predictors of success of radiofrequency catheter ablation for atrial flutter (AFL). We examined the relationship between the sizes of cavotricuspid isthmus as measured by multidetector-row computed tomography (MDCT) and fluoroscopy. We used eight-detector MDCT to measure the tricuspid isthmus of 23 patients prior to linear ablation for common AFL. One patient with a deep pouch in the RA was excluded. Parameters measured were (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…4 Recently, MDCT and three-dimensional intracardiac echography can provide more detailed intracardiac structure and could be helpful for increasing the efficiency of AFL ablation. 4,5 In this patient, a long vertical vestibule and diverticulumlike morphology of CTI that has not been described before was demonstrated in the right anterior oblique projection of the right atrial angiography. By using the conventional continuous pullback technique, the CTI was difficult to be ablated completely because of complex morphology of CTI.…”
Section: Figure 1 Tracings Show the Surface Ecg Of Leads II Iii V1supporting
confidence: 55%
See 1 more Smart Citation
“…4 Recently, MDCT and three-dimensional intracardiac echography can provide more detailed intracardiac structure and could be helpful for increasing the efficiency of AFL ablation. 4,5 In this patient, a long vertical vestibule and diverticulumlike morphology of CTI that has not been described before was demonstrated in the right anterior oblique projection of the right atrial angiography. By using the conventional continuous pullback technique, the CTI was difficult to be ablated completely because of complex morphology of CTI.…”
Section: Figure 1 Tracings Show the Surface Ecg Of Leads II Iii V1supporting
confidence: 55%
“…Three different angiographic morphologies of CTI were reported with straight, concave, and pouch‐like recesses in which concave morphology and pouch‐like recesses CTI would account for much longer ablation time 4 . Recently, MDCT and three‐dimensional intracardiac echography can provide more detailed intracardiac structure and could be helpful for increasing the efficiency of AFL ablation 4,5 . In this patient, a long vertical vestibule and diverticulum‐like morphology of CTI that has not been described before was demonstrated in the right anterior oblique projection of the right atrial angiography.…”
Section: Discussionmentioning
confidence: 62%
“…Among these CTI variations, the presence of a pouch, long CTI, and prominent Eustachian ridge/valve have been shown to be the factors related to a longer RF duration. 4,5,8,11,12 Da Costa, et al 4 reported that the CTI characteristics, such as the concavity and the presence of a pouch, are the factors that increase the procedure duration. In particular, the presence of a pouch increased the RF duration even though the length of the CTI was short.…”
Section: Cti Anatomy and Radiofrequency Ablationmentioning
confidence: 99%
“…7 Recently, various imaging studies, including angiography, multiple-detector computed tomography, transthoracic echocardiography (TTE), transesophageal echocardiography, and intracardiac echocardiography (ICE), have been used to evaluate the isthmus. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] In particular, using ICE provides a direct visualization and detailed assessment of the CTI anatomy and facilitates the ablation procedure. 7,[14][15][16][17] However, to the best of our knowledge, there have been no studies that have investigated the geometry of the CTI precisely with ICE and the occasional need for a knuckle-curve ablation during the CTI ablation.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies showed that the specific anatomy of the CTI may be one of the causes for the difficulties with non-successful CTI ablation [4][5][6][7][8][9]. Evidence for such anatomical characteristics has been reported by angiographic studies [6,7], multi-slice computed tomography [10,11], and cardiac magnetic resonance (CMR) imaging study [8,9]. In addition, the endocardial surface complexity, wall thickness along the CTI [4,7,11], and ablation mediated tissue edema might play a crucial role in formation of conduction gaps and non-transmural lesions along the ablation line [5,[12][13][14].…”
Section: Introductionmentioning
confidence: 97%